Aromatic Structure Influence on the Selectivity of Substituted Methacryloylaminophenylmethacrylates Free-Radical Polymerization - Vretik, L. O.; Nikolaeva, O. A.; Zagniy, V. V.; Syromyatnikov, V. G. (Київський національний університет імені Тараса Шевченка, 2013)
A new dimethacrylic monomer with biphenylbenzoate-type aromatic core was tested to the possibility to carry out its selective homopolymerization under conditions of thermoinitiated radical polymerization in DMF solution. The kinetics of thermo-induced radical homopolymerization of this monomer as well as some model compounds were studied by dilatometry. The preferring polymerization of O-methacryloyl double bond was proved by 1H NMR spectroscopy.
Keywords: methacryloylaminophenylmethacrylates; radical polymerization